the Penggunaan Media Sosial dalam Pendidikan Kedokteran dengan Konsep E-learning: Penggunaan Media Sosial dalam Pendidikan Kedokteran dengan Konsep E-learning - Della inike Putri; Evi Kurniawaty (CV. Jasa Sukses Abadi, 2021)
Social media is one of the online media that often used by the wider community to convey information to others and play an important role in the education process. Social media also provides the concept of space to interact and share knowledge by providing group facilities for students who join and discuss various topics, collaborate and use educational applications to manage learning activities. Medicine is one of the fields that has gained an important foundation through the application of one concept such as e-learning. To formulate learning with an effective e- learning system, collaboration must occur between educational institutions, instructors and technology experts. Although the use of the internet as a learning medium is very potential, not all learning materials can be replaced through social networks. In the learning process, the use of social networking is more stimulating cognitive abilities of medical students, but the skills and motor skills to conduct physical examination, history taking, practicum, and affective assessment of students should still be done face-to-face learning.